Evaluation of the Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) III in Aceh Jaya Regency - Papat Maliki (Journal of Social Research, 2025)
The provision of community-based drinking water and sanitation is a program aimed at addressing sanitation problems. This study evaluates the performance of clean water services and management through the PAMSIMAS III Program in Aceh Jaya Regency from 2017 to 2023. Using qualitative methods, secondary data from the PAMSIMAS website, and primary data from village heads, communities, and the PAMSIMAS III team were analyzed descriptively. The research was conducted in selected villages of Aceh Jaya, chosen as recipients of the PAMSIMAS III program, to increase public awareness of drinking water provision. The evaluation criteria effectiveness, efficiency, adequacy, equity, and responsiveness show that the PAMSIMAS III program has been successfully implemented but not optimally. Key challenges include limited human resource quality, under-functioning institutions, and poor communication and coordination. For rural communities receiving PAMSIMAS III assistance, socialization on healthy lifestyles and environmental care is necessary. Implementing institutions are encouraged to establish a dedicated forum to improve inter-agency coordination. Local government policies and strategies should focus on attracting investors to support the development and management of drinking water, sanitation, and environmental sustainability in Aceh Jaya Regency. Finally, strengthening the commitment and consistency of village officials and communities in managing clean water facilities is essential to ensure long-term access to clean water.